2016
DOI: 10.1017/s0954422416000111
|View full text |Cite
|
Sign up to set email alerts
|

Association between obesity and asthma – epidemiology, pathophysiology and clinical profile

Abstract: Obesity is a risk factor for asthma, and obese asthmatics have lower disease control and increased symptom severity. Several putative links have been proposed, including genetics, mechanical restriction of the chest and the intake of corticosteroids. The most consistent evidence, however, comes from studies of cytokines produced by the adipose tissue called adipokines. Adipokine imbalance is associated with both proinflammatory status and asthma. Although reverse causation has been proposed, it is now acknowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 157 publications
(175 reference statements)
1
29
0
2
Order By: Relevance
“…Our findings are consistent with a meta‐analysis of 31 European cohort studies that identified that a higher infant weight gain in premature infants was associated with preschool wheezing and childhood asthma . Obesity during puberty has been linked to increased growth velocity in the first years of life and obesity is associated with childhood asthma . A proposed mechanism for this association is the release of immunomodulatory cytokines from adipose tissue leading to airway hyper‐responsiveness or through mechanical restriction of the chest wall; however, the association between asthma and obesity is often confounded by deconditioning …”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our findings are consistent with a meta‐analysis of 31 European cohort studies that identified that a higher infant weight gain in premature infants was associated with preschool wheezing and childhood asthma . Obesity during puberty has been linked to increased growth velocity in the first years of life and obesity is associated with childhood asthma . A proposed mechanism for this association is the release of immunomodulatory cytokines from adipose tissue leading to airway hyper‐responsiveness or through mechanical restriction of the chest wall; however, the association between asthma and obesity is often confounded by deconditioning …”
Section: Discussionsupporting
confidence: 88%
“…36 Obesity during puberty has been linked to increased growth velocity in the first years of life 37 and obesity is associated with childhood asthma. [38][39][40] A proposed mechanism for this association is the release of immunomodulatory cytokines from adipose tissue leading to airway hyper-responsiveness or through mechanical restriction of the chest wall; however, the association between asthma and obesity is often confounded by deconditioning. 39 We found that tracheal colonization in the neonatal period was associated with a decreased risk of asthma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…49 Atopic asthma is characterized by high eosinophil, mast cell, and T-lymphocyte counts, whereas nonatopic asthma displays high neutrophil and mast cell counts. 49 Muc et al 50 reported that the main change in obese asthmatic patients was the shift of immune response from T H 2 (a typical atopic immunologic profile) to T H 1. Thus the type of airway inflammation driven mainly by neutrophils 51 in obese subjects might partially explain the stronger relationship of obesity with later-onset and nonatopic asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Comorbidities directly associated with excess body fat include T2DM, certain cancers and cardiovascular diseases including hypertension, coronary artery disease and stroke 9 . More severe cases of obesity are associated with an increased incidence of sleep apnea 10,11 , asthma [12][13][14] , gallstones 15 , steatohepatitis 16 , glomerulosclerosis 17 , dyslipidaemia and endothelial dysfunction 18,19 . The metabolic complications linked to obesity are often attributed to systemic processes such as metabolic inflammation or cellular pathologies such as mitochondrial dysfunction 20 and/or stress of the endoplasmic reticulum due to lipotoxicity 19,21 .…”
Section: Human Obesity -Hallmark Manifestationsmentioning
confidence: 99%